Relationships between big‐five personality factors and Alzheimer's disease pathology in autosomal dominant Alzheimer's disease. Issue 1 (23rd June 2020) - Aschenbrenner, Andrew J.; Petros, Jennifer; McDade, Eric; Wang, Guoqiao; Balota, David A.; Benzinger, Tammie LS; Cruchaga, Carlos; Goate, Alison; Xiong, Chengjie; Perrin, Richard; Fagan, Anne M.; Graff‐Radford, Neill; et al.
Abstract: Introduction: Changes in personality characteristics are associated with the onset of symptoms in Alzheimer's disease (AD) and may even precede clinical diagnosis. However, personality changes caused by disease progression can be difficult to separate from changes that occur with normal aging. The Dominantly Inherited Alzheimer Network (DIAN) provides a unique cohort in which to relate measures of personality traits to in vivo markers of disease in a much younger sample than in typical late onset AD. Methods: Personality traits measured with the International Personality Item Pool at baseline from DIAN participants were analyzed as a function of estimated years to onset of clinical symptoms and well‐established AD biomarkers. Results: Both neuroticism and conscientiousness were correlated with years to symptom onset and markers of tau pathology in the cerebrospinal fluid. Self‐reported conscientiousness and both neuroticism and conscientiousness ratings from a collateral source were correlated with longitudinal rates of cognitive decline such that participants who were rated as higher on neuroticism and lower on conscientiousness exhibited accelerated rates of cognitive decline. Discussion: Personality traits are correlated with the accumulation of AD pathology and time to symptom onset, suggesting that AD progression can influence an individual's personality characteristics. Together these findings suggest that measuring neuroticism and conscientiousness may hold utility in tracking disease progression in AD.